Technological Innovation as a Factor of Demand for Energy Sources in Automotive Industry - Tatiana Mitrova; Vyacheslav Kulagin; Dmitriy Grushevenko; Ekaterina Grushevenko (Foresight and STI Governance, 2015)
The issue of forecasting demand for liquid fuels has become particularly significant in recent years with technological development and much tougher inter-fuel competition in the transport sector. In future, these developments could radically transform the oil, gas, and electricity markets. Therefore there is a greater need for improved forecasting methods that take into account the dynamics of market factors, primarily those related to the use of new technologies. We analyse the difficulties of forecasting demand for liquid fuels in conditions of uncertainty related to future technological developments in car transport. We classify the technologies driving demand for motor fuels by the nature of their impact on the demand for petroleum products: technologies aimed at improving the energy efficiency of traditional cars, as well as drivers of inter-fuel competition, both in terms of direct and indirect substitutes for petroleum products. To resolve the problem of limited input information, the methodology incorporates clustering instruments, which enable us to group countries according to certain criteria. The use of economic and mathematical tools with optimizing units enables us to make integrated calculations that model the market for liquid fuels and assess its interactions with the markets of other energy resources. Our proposed system for forecasting demand for liquid fuels, including petroleum products, can be used as an instrument to assess the future impact of technological innovation on the development of the oil industry when carrying out Foresight studies.